Management of paediatric high‐grade blunt renal trauma: a 10‐year single‐centre UK experience. (14th February 2018) - Wong, Kee Y.; Jeeneea, Ram; Healey, Andrew; Abernethy, Laurence; Corbett, Harriet J.; McAndrew, Helen F.; Losty, Paul D.
Abstract : Objective: To report the management and outcome of paediatric patients sustaining high‐grade blunt renal trauma. Patients and Methods: Medical records were examined for all American Association for the Surgery of Trauma (AAST) grade III–V blunt renal trauma cases admitted to a paediatric trauma centre from 2005 to 2015. Data collected and analysed included: demographics, imaging modalities, management, length of hospital stay (LOS), complications, and follow‐up outcomes. Results: In all, 18 children (12 boys, six girls) with mean (range) age 11 (4–15) years were included. According to the AAST grading criteria, 39% (seven of 18) of the patients had grade III, 50% (nine of 18) grade IV, and 11% (two of 18) grade V injuries; 44% (eight of 18) had concomitant injuries. Most of the patients were managed conservatively (89%, 16 of 18), although two of the 16 subsequently needed JJ‐stent insertion during inpatient stay for symptomatic urinoma(s). In all, 11% (two of 18) of the patients required interventional radiology service(s), involving selective embolisation for life‐threatening renal tract haemorrhage. Blood transfusion for renal injury exclusively was required in 11% (two of 18) of the patients. In all, 89% (16 of 18) of the patients had at least one follow‐up imaging study before hospital discharge; most (13 of 16) had ultrasonography and three required computed tomography. The median (range) LOS was 11 (4–31) days. In all, 17% (three of 18) of the patients required hospital re‐admission within 30 days for complications and all required interventional procedures: JJ stent for urinoma (one), embolisation of renal arterio‐venous fistula (one), and embolisation for a post‐traumatic pseudoaneurysm (one). Overall, the median (range) follow‐up was 6 (2–60) months. In all, 78% (14 of 18) of the patients had dimercaptosuccinic acid studies, with 11 showing reductions in renal function (range 3–44%). Conclusions: This study supports a care pathway strategy advocating conservative management of high‐grade renal injuries in children. However, patients may experience a relative decline in renal function with higher grade injuries indicating the need for monitoring and follow‐up.